(untitled) (Journal of Social Sciences Review, 2024)
In space exploration, astronaut health and safety are crucial. The harsh circumstances of space need a thorough review of the laws that protect people who journey there. This article uses the doctrinal approach to examine the particular issues of space missions and how to keep astronauts healthy and safe. The article begins with an overview of these problems and emphasizes astronaut health and safety, then examines how space law has developed to handle health concerns. The examination examines relevant laws, treaties, and regulations for astronaut well-being using a doctrinal perspective. Additionally, it discusses how international space accords and agreements promote astronaut health and safety. The study also examines how national regulations and space agencies enforce these restrictions. A complete review of pre-mission assessments, in-flight medical assistance, and post-mission health monitoring follows. Also discussed are astronauts’ mental health and support networks. After discussing potential issues, the article recommends additional study and regulation to protect astronauts.